Lipid lowering effects of oyster mushroom (Pleurotus ostreatus) in humans - Inga Schneider; Gaby Kressel; Annette Meyer; Ulrich Krings; Ralf G Berger; Andreas Hahn (Journal of Functional Foods, 2011)
Elevated cholesterol and triacylglycerol levels are known risk factors for cardiovascular diseases. A number of animal studies have indicated that the consumption of oyster mushrooms (Pleurotus ostreatus) can positively influence the lipid profile. The present intervention study for the first time investigated the cholesterol lowering properties of an oyster mushroom diet in humans. A total of 20 subjects (9 male, 11 female; 20–34 years) were randomized to take either one portion of soup containing 30 g dried oyster mushrooms or a tomato soup as a placebo on a daily basis for 21 days. Standardized blood concentrations of lipid parameters and oxidized low density lipoprotein were measured at the baseline (t0) and after 21 days (t21). Treatment with oyster mushroom soup decreased triacylglycerol concentrations (−0.44 mmol/L; p = 0.015) and oxidized low density lipoprotein levels (−7.2 U/mL; p = 0.013) significantly, and showed a significant tendency in lowering total cholesterol values (−0.47 mmol/L; p = 0.059). No effects on low density lipoprotein and high density lipoprotein levels were found. The beneficial effects of oyster mushroom on blood serum parameters may be attributed to the presence of linoleic acid, ergosterol and ergosta-derivatives which showed notable activity in oxygen radical absorbance capacity and cyclooxygenase inhibition assays in vitro.